Nursing of a patient with chemotherapy-induced oral ulcer treated with Traditional Chinese Medicine mouthwash combined with moxibustion (中药含漱疗法联合艾灸治疗化疗相关性口腔溃疡1例的护理) - LI Fang (李芳); LIU Shuhong (刘书红); ZHAO Yanan (赵亚楠); ZHAO Yan (赵燕) (中西医结合护理)
To summarize the nursing of a liver cancer patient with chemotherapy-induced oral ulcer, and provide reference for clinical practice. Traditional Chinese Medicine mouthwash (30 min per time, four times a day) was administrated for relieving external heat, moistening dryness, and promoting fluid production. After using ginger slice to embrocate local skin, the moxa stick moxibustion at Zusanli and Yongquan acupoints was carried out once a day for 30 minutes each time. The patient's oral ulcer pain decreased and the ulcer surface shrank after treatment. Traditional Chinese Medicine mouthwash therapy combined with moxa stick moxibustion after embrocation using ginger is effective to relieve chemotherapy-induced oral ulcers and improve patient quality of life. (总结1例肝癌患者化疗相关性口腔溃疡的护理经验, 为临床提供指导。采用解表透热润燥生津中药含漱, 4次/d, 30 min/次; 生姜涂擦治疗部位皮肤后再进行足三里、涌泉穴艾条灸, 1次/d, 30 min/次。患者的口腔溃疡疼痛减轻、溃疡面缩小。对口腔溃疡患者施以中药含漱疗法联合艾条灸, 可改善化疗相关性口腔溃疡, 有助于改善患者生活质量, 具有较高的应用价值。)